Risk of second primary malignancies in women with breast cancer: Results from the European prospective investigation into cancer and nutrition (EPIC). Issue 4 (13th February 2015) - Ricceri, Fulvio; Fasanelli, Francesca; Giraudo, Maria Teresa; Sieri, Sabina; Tumino, Rosario; Mattiello, Amalia; Vagliano, Liliana; Masala, Giovanna; Quirós, J. Ramón; Travier, Noemie; Sánchez, María‐José; Larranaga, Nerea; et al.
<x xml:space="preserve">Abstract</x> Women with a diagnosis of breast cancer are at increased risk of second primary cancers, and the identification of risk factors for the latter may have clinical implications. We have followed‐up for 11 years 10, 045 women with invasive breast cancer from a European cohort, and identified 492 second primary cancers, including 140 contralateral breast cancers. Expected and observed cases and Standardized Incidence Ratios (SIR) were estimated using Aalen‐Johansen Markovian methods. Information on various risk factors was obtained from detailed questionnaires and anthropometric measurements. Cox proportional hazards regression models were used to estimate the role of risk factors. Women with breast cancer had a 30% excess risk for second malignancies (95% confidence interval—CI 18–42) after excluding contralateral breast cancers. Risk was particularly elevated for colorectal cancer (SIR, 1.71, 95% CI 1.43–2.00), lymphoma (SIR 1.80, 95% CI 1.31–2.40), melanoma (2.12; 1.63–2.70), endometrium (2.18; 1.75–2.70) and kidney cancers (2.40; 1.57–3.52). Risk of second malignancies was positively associated with age at first cancer, body mass index and smoking status, while it was inversely associated with education, post‐menopausal status and a history of full‐term pregnancy. We describe in a large cohort of women with breast cancer a 30% excess of second primaries. Among risk factors for breast cancer, a history of full‐term pregnancy was inversely associated with the risk of second primary cancer.